-7+8b=-11+8b+8-4

Simple and best practice solution for -7+8b=-11+8b+8-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7+8b=-11+8b+8-4 equation:



-7+8b=-11+8b+8-4
We move all terms to the left:
-7+8b-(-11+8b+8-4)=0
We add all the numbers together, and all the variables
8b-(8b-7)-7=0
We get rid of parentheses
8b-8b+7-7=0
We add all the numbers together, and all the variables
=0
b=0/1
b=0

See similar equations:

| -12p+3p=11(p+14) | | x*x=180 | | y(2y+1)+10=0 | | 5x^2+6x=-3x^2+2x | | 42=6k+3 | | (x-1)^3=8 | | -12=a-2 | | j/6+41=45 | | 96=8(n+1) | | 2h+4-55=-3h+4 | | 5x+14=109 | | Y=117.8+-1.4x | | 16=-2h | | 5(3v-4)=40+3v | | 1/2(x+12=4x-1 | | 4=y-77/5 | | 3+14y-1=8y+52-4y | | 25d+5=80 | | 12=2+y | | 0.25x=5+5 | | y/2-10=28 | | P=129p=108 | | 5k-10÷2=-7 | | y-(-10)=-6 | | 14u=60 | | 6(^x+2)=12 | | 9+3y-4=7y+5-3y | | (7-v)(5v-8)=0 | | 11r+-77=-88 | | 9+3y-4=7y+5-37 | | -12s=-60 | | 10=-7x+6x+4 |

Equations solver categories